Objective Assessment of Back Kinematics and Movement Asymmetry in Horses: Effect of Elastic Resistance Band Training. (September 2015) - Simons, V.; Weller, R.; Stubbs, N.C.; Rombach, N.; Pfau, T.
Abstract : Reasons for performing study: Training and rehabilitation techniques which improve core muscle strength are beneficial for improvement of dynamic stability of the equine vertebral column. The Equiband™ system, consisting of resistance bands attached to a customised saddle pad, is suggested to provide constant proprioceptive feedback during motion to encourage recruitment of abdominal and hindquarter musculature. Objectives: To quantify the effect of the Equiband™ system on back kinematics and movement symmetry. Study design: Longitudinal intervention study. Methods: Quantitative analysis of back movement and gait symmetry before/after a 4‐week exercise programme. Inertial sensor data was collected from 7 horses at Weeks 0 and 4 of a fixed exercise protocol. Analysis with and without the Equiband™ system was completed at trot in hand on a hard surface, and for both reins on the lunge on a soft surface. Six back kinematic and 3 movement symmetry parameters were calculated according to published methods. Movement symmetry values were side‐corrected to allow comparison between reins on the lunge. A mixed model (P<0.05) evaluated the effects of the Equiband™ system over time, and trotting direction on back kinematic and movement symmetry parameters. Results: The Equiband™ system significantly reduced (all P<0.02) roll, pitch and mediolateral displacement in the cranial‐mid thoracic region. Across all horses, back displacement and range of motion values were significantly greater (P<0.01) on the lunge than in a straight line, movement symmetry was consistent with having corrected all horses to be left‐sided. Conclusion: Preliminary results suggest the Equiband™ system may aid dynamic stabilisation of the vertebral column. Ethical animal research: This study was authorised by the Ethics and Welfare Committee of the Royal Veterinary College, London (URN Approval Number 1238). Written consent was obtained from the owner/keeper of each animal.Source of funding: Royal Veterinary College.Competing interests: N.C. Stubbs and N. Rombach developed the Equiband™ system. The remaining authors have no competing interests.